KEPEMIMPINAN KEPALA SEKOLAH DALAM PENGELOLAAN MADRASAH (TINGKAT MTS DAN MA) - Alfi Sukrina; Nur ‘Azizah, Cipto Halomoan, Darul Ilmi (CAPITALIS: JOURNAL OF SOCIAL SCIENCES, 2023)
The aim of this research is to examine what madrasa management (MTS and MA levels) must be regulated by school principals based on literature. This research uses the literature study method. Data sources are taken from trusted sources such as books, journal articles and documents that discuss the performance of school principals in leadership. The research results obtained are that a school is a leader in an educational unit, therefore a leader has functions and duties in carrying out tasks that function as first, a medium for achieving organizational goals and, influencing or motivating other parties. The main aim of leadership is to influence or motivate other people/parties to become actively involved in the organization's working mechanisms, so that leadership can be said to be successful if it is able to influence and motivate other people or parties to jointly achieve the stated organizational goals. In managing madrsahs, school principals are also regulated by law.